The Influence of Airport Image and Facility Functionality on Word of Mouth: The Mediating Role of Positive Emotions - Rahayuningsih, Titien; Ruslan, Ruslan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the influence of airport image and facility functionality on passengers’ word-of-mouth behavior by examining the mediating role of positive emotions. As airports increasingly evolve into complex service environments, understanding how physical and perceptual attributes shape passengers’ emotional responses and behavioral intentions becomes strategically important. A quantitative research design was employed using a survey method involving 385 passengers at halu oleo kendari airport, indonesia. Data were analyzed using structural equation modeling–partial least squares (sem-pls) to test both direct and indirect relationships among the proposed constructs. The findings reveal that airport image and facility functionality have significant direct effects on positive emotions, travel intention, and word-of-mouth communication. Moreover, positive emotions play a crucial mediating role in strengthening the relationships between airport image and travel intention, as well as between facility functionality and word-of-mouth behavior. The results demonstrate that well-functioning airport facilities and a favorable airport image enhance passengers’ emotional experiences, which subsequently increase their intention to travel and their willingness to recommend the airport to others. From a theoretical perspective, this study contributes to the airport management and consumer behavior literature by empirically validating positive emotions as a key psychological mechanism linking airport attributes to behavioral outcomes. Practically, the findings provide valuable insights for airport managers to prioritize improvements in facility performance and image-building strategies in order to foster positive passenger emotions, enhance loyalty, and stimulate favorable word-of-mouth promotion. Future research is encouraged to incorporate additional moderating variables and expand the study across multiple airport contexts.